2019
DOI: 10.1108/jedt-03-2019-0052
|View full text |Cite
|
Sign up to set email alerts
|

The role of knowledge sharing in supply chain success

Abstract: Purpose The aim of this paper is to provide a comprehensive and detailed review of the state-of-the-art mechanisms of knowledge sharing (KS) in the supply chain (SC) field, as well as directions for future research. Briefly, this paper tries to offer a systematic and methodical review of the KS mechanisms in the SC to provide a comparative summary of the selected articles, to collect and describe the factors that have the influence on KS and SC, to explore some main challenges in this field and to present the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 73 publications
(79 reference statements)
0
14
1
Order By: Relevance
“…Alavi and Leidner (2001) declared that IT tools and capabilities play a significant role in knowledge‐sharing systems in terms of promoting the organizational flow of knowledge processes and extending the limits of communication lines. Rajabion et al (2019) emphasized the importance of knowledge‐sharing to sustain flexibility and competitiveness for the organizations thus, the combination of the knowledge‐sharing with innovative activities in SC, on the other hand, can boost an organization's competitive advantage. Furthermore, technological innovations in SC will help to improve production efficiency, distinguishes consumption of natural resources which finally leads green business growth and economic growth (Fernandes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alavi and Leidner (2001) declared that IT tools and capabilities play a significant role in knowledge‐sharing systems in terms of promoting the organizational flow of knowledge processes and extending the limits of communication lines. Rajabion et al (2019) emphasized the importance of knowledge‐sharing to sustain flexibility and competitiveness for the organizations thus, the combination of the knowledge‐sharing with innovative activities in SC, on the other hand, can boost an organization's competitive advantage. Furthermore, technological innovations in SC will help to improve production efficiency, distinguishes consumption of natural resources which finally leads green business growth and economic growth (Fernandes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge sharing can be seen as the provision of expertise in order to assist others and collaborate with them to address and solve challenges, improve new ideas, or enforce policies and actions (Rajabion et al, 2019). Knowledge sharing across various supply chain tiers (multi‐tier) often help to improves company's capacity to foresee or sense major shifts in global economic, legal, and political environments in order to reshape supply chain activities in reaction to those changes (Nix, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…(Materia et al, 2017) Cloud computing supports the inter-organizational design and implementation of open innovation (Loukis et al, 2017) Bricolage Collaborative encourages organizations to share resources with partners and actively contribute to the emergence of desired new products (Gurca & Ravishankar, 2016) Networking capability in product innovation has an impact on supplier relationships, as well as overall organizational performance (Mitrega et al, 2017) Supply chain intelligence (technological knowledge, sourced and integrated from suppliers, customers and competitors) plays an important role in the successful launch of new products (Schoenherr & Swink, 2015) Internal collaboration (exploitative learning) and external competencies, which include supply network flexibility and supplier operational capabilities (exploratory learning), increase the contribution to innovation capability. (Liao & Li, 2019) Knowledge sharing helps increase supply chain innovation (Rajabion et al, 2019) The involvement of external consultants helps the organization to be able to utilize the acquired technology knowledge to achieve the highest innovation performance at the lower levels of R&D outsourcing (Bianchi et al, 2016) Effective cross-cultural interaction is one of the essential requirements for the development of innovative business strategies and the achievement of competitive advantage in modern global markets. (Milovanovic, 2015) Big Data Analytics is able to manage data security and impact supply chain innovation service capabilities and supply chain service performance.…”
Section: Publications Year Of Innovation Studies In Collaboration Netmentioning
confidence: 99%
“…Cloud computing Design and implementation of interorganizational open innovation (Loukis et al, 2017) Sharing resources New product (Gurca & Ravishankar, 2016) Supply chain intelligence New product launching (Schoenherr & Swink, 2015); Internal collaboration and external competence Innovation capabilities (Liao & Li, 2019) Open Innovation Knowledge sharing Supply chain innovation (Rajabion et al, 2019); External consultant involvement Innovation performance (Bianchi et al, 2016)…”
Section: According Tomentioning
confidence: 99%
“…Knowledge sharing positively influences supply chain agility, where suppliers and buyers provide helpful information for supply chain relationships (Kim & Chai, 2017). Other empirical evidence was also found that knowledge sharing affects supply chain agility (Rajabion et al, 2019: Mehdikhani & Valmohammadi, 2019.…”
Section: Knowledge Sharing and Supply Chain Agilitymentioning
confidence: 93%